Assessing European competitiveness: the new CompNet microbased database - Paloma Lopez-Garcia; Filippo di Mauro (European Central Bank (ECB), 2015)
Drawing from confidential firm-level balance sheets for 17 European countries (13 Euro-Area), the paper documents the newly expanded database of cross-country comparable competitiveness-related indicators built by the Competitiveness Research Network (CompNet). The new database provides information on the distribution of labour productivity, TFP, ULC or size of firms in detailed 2-digit industries but also within broad macrosectors or considering the full economy. Most importantly, the expanded database includes detailed information on critical determinants of competitiveness such as the financial position of the firm, its exporting intensity, employment creation or price-cost margins. Both the distribution of all those variables, within each industry, but also their joint analysis with the productivity of the firm provides critical insights to both policy-makers and researchers regarding aggregate trends dynamics. The current database comprises 17 EU countries, with information for 56 industries, including both manufacturing and services, over the period 1995-2012. The paper aims at analysing the structure and characteristics of this novel database, pointing out a number of results that are relevant to study productivity developments and its drivers. For instance, by using covariances between productivity and employment the paper shows that the drop in employment which occurred during the recent crisis appears to have had “cleansing effects” on EU economies, as it seems to have accelerated resource reallocation towards the most productive firms, particularly in economies under stress. Lastly, this paper will be complemented by four forthcoming papers, each providing an in-depth description and methodological overview of each of the main groups of CompNet indicators (financial, trade-related, product and labour market).
Keywords: L11; L25; D24; O4; O57; 330; allocative efficiency; competitiveness; cross country analysis; firm-level data; productivity and size distribution; total factor productivity; Industrie; Dienstleistungssektor; Internationaler Wettbewerb; Querschnittsanalyse; Betriebswirtschaftliche Produktionsfunktion; Produktivitätsentwicklung; Arbeitsproduktivität; Europa